The unique characters and habitat of Freycinetia (Pandanaceae) with seven new species in Timika, West Papua, Indonesia - Nurhaidah Iriany Sinaga; Ary Prihardhyanto Keim; Pratita Puradyatmika (Research Center for Biology, 2013)
This current study of Freycinetia was carried out in Timika, West Papua. Results indicate that species vary in both morphological characters and habitat preferences. Timika is unique as only in this area species with highest number of segments in a berry and of stigmatic remains are found. Exceptional characters regarding to auricles, areolas, and stigmatic remains are observed in many species in this area. The result of this current study suggests that the ability of species to adapt to the widespread forest disturbances in Timika leads to their differences in morphological features compare to other Papuan species. Subsequently, seven new species are described here.